Permodelan Teori Penggiliran bagi Proses Permohonan Kad Pengenalan di Jabatan Pendaftaran Negara, Malaysia - Mohd. Noor, Mat Taharim (2004)
At the outset, this study is conducted with the aim to observe the significant of the operational research methodology application, in particular the queue theory model, in analyzing service time frame with a view to improving the service quality of JPNPJ. Hence, data pertaining to the service time duration, which include waiting and service time are being studied and tested to ascertain whether the application of the mentioned scientific approach could produce encouraging results that would be able to solve queue problem facing JPNPJ . Information pertaining to customers’ arrival during the research period, from 7.30 a.m. till 4.45 p.m. Monday to Friday, excluding time from 12.15 p.m. till 2.45 p.m. on Friday only, for five days period between August, 9 and August, 13 2004 in Phase I, and between September, 13 and September, 17 2004 in Phase II are being collated for the research purposes. Data are also retrieved from the JPNPJ database system pertaining to customers’ arrival and service time in Phase I and Phase II (arrival time only). Details of service time in Phase II are recorded personally by the researcher. Next, the Statistical Package for Social Survey (SPSS) software with a Kolmogorov-Smirnov non-parametric test was applied to determine whether the arrival rate and service rate follow a Poisson and Exponential distribution respectively. Having done that, QM for Window software was applied to determine the operating characteristics for M/M/s (Multiple Servers with Exponential Service) in order to analyze the requirement of exact number of servers vis-a-vis JPNPJ queue problem. The above notwithstanding, this study was able to achieve the stated research objectives, as the data (arrival and service time) met the queue theory requirements. Nevertheless, a more precise analysis and significant results could be achieved if a better lambda [I] and miu [p] was obtained from a much longer research time frame. Certainly, an improved service quality of JPNPJ and a fine-tuned Client’s Charter would enhance public positive opinion of the said organization.